Encouraging Interest in Music - Repar, Lavra (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter summarizes studies investigating ways to promote interest in music. Research into student musical preferences reveals that musical taste evolves throughout life, with younger generations often demonstrating a greater willingness to explore diverse musical genres. Alongside musical taste and preferences, factors such as gender and personality traits also influence music selection. Teachers who adapt learning content to align with students' interests observe higher levels of motivation and engagement. Furthermore, incorporating project-based approaches that foster creativity and long-term musical involvement plays a key role in sustaining students' interest in music.